SENSORY QUALITY OF ROASTED COFFEE BEANS UNDER DIFFERENT STORAGE CONDITIONS - Nadaleti, Denis Henrique Silva; Rocha, Hully Alves; Mendonça, Luciana Maria Vieira Lopes; Mendonça, José Marcos Angélico de; Reis, Iêda Bruna dos; Evaristo, Carlos Henrique; Terra, Sávia Del Vale (Coffee Science - ISSN 1984-3909, 2019)
Roasted coffee is subject to loss of quality due to aging, and the intensity of these losses is influenced by packaging. The objective in this study was to evaluate the possible losses in the sensory quality of a specialty roasted coffee, stored in beans for 150 days in different packages and storage temperatures. The experiment was carried out in the Coffee Classification and Industrialization Laboratories of IFSULDEMINAS Campus Muzambinho. The coffee was roasted and after 48 hours it was packed in three different packages and kept stored at room temperature and refrigerated at 18ºC ± 1ºC for 150 days, with evaluations every 50 days, starting from zero time. The experimental design used was entirely randomized with 3 repetitions. Sensory evaluation was performed by three Q-Grader judges, according to the SCAA protocol. The data were evaluated using the SISVAR software, and when significance between treatments was detected, the regression and Scott-Knott tests were applied at the 5% probability level. The packaging used for storage did not interfere in the quality of the coffee. There was an interaction between temperature and storage time for the sensory attribute “body”. The quality decreased linearly with the storage time, from 86 to 80 points, to 84 days of storage.